Nanophotonic method and sensor for polycyclic aromatic hydrocarbons detection - Sushko, O. A.; Bilash, О. М.; Rozhitskii, M. M. (ECL 2014, 2014)
Anthropogenic pollution of environmental water is a huge problem for humanity today as it leads to an increase of incurable diseases. For example, the penetration into the organism of organic carcinogens such as polycyclic aromatic hydrocarbons (PAHs) can lead to the development of cancer tumors. Among PAHs the most dangerous is 3,4-benzopyrene (BP). There are a number of analytical methods for BP detection such as chromatographic, immuno-chemical, spectroscopic, luminescent and biological methods. But these methods beside their advantages have a number of significant shortcomings such as high detection limit (immuno-chemical and biological method), insufficient selectivity of PAHs detection, complexity and duration of sample preparation and analysis, high cost of device. Therefore development of new methods and tools for PAHs detecting using modern nanotechnology and nanomaterials remains urgent. So this work is devoted to the development of nanophotonic method and sensor device construction for the PAH in particular BP detection in water environment objects. Nanomaterials such as spherical quantum dots (QDs) are perspective object of nanophotonics can be used for development of optical sensors as sensor’s detector elements. They have a high luminescence quantum yield, possibility of optical and non-optical excitation, narrow luminescence spectrum and its wavelength dependence on the QDs diameter, high selectivity. This defined the perspective of their use instead of the well known organic luminophores.
Keywords: nanophotonic method; nanophotonic sensor; polycyclic aromatic hydrocarbons; spherical quantum dots